Moyamoya Disease With Initial Ischemic or Hemorrhagic Attack Shows Different Brain Structural and Functional Features: A Pilot Study - Hu, Junwen; Li, Yin; Tong, Yun; Li, Zhaoqing; Chen, Jingyin; Cao, Yang; Zhang, Yifan; Xu, Duo; Zheng, Leilei; Bai, Ruiliang; Wang, Lin (Frontiers in Neurology, 2022)
Objective – Cerebral ischemia and intracranial hemorrhage are the two main phenotypes of moyamoya disease (MMD). However, the pathophysiological processes of these two MMD phenotypes are still largely unknown. Here, we aim to use multimodal neuroimaging techniques to explore the brain structural and functional differences between the two MMD subtypes. Methods – We included twelve ischemic MMD, ten hemorrhagic MMD patients, and ten healthy controls (HC). Each patient underwent MRI scans and cognitive assessment. Cortical thickness of the two MMD subtypes and HC group were compared. Arterial spin labeling (ASL) and diffusion tensor imaging (DTI) were used to inspect cerebral blood flow (CBF) of the cortical regions and the integrity of the related white matter fibers, respectively. Correlation analyses were then performed among the MRI metrics and cognitive function scores. Results – We found that only the cortical thickness in the right middle temporal gyrus (MTG) of hemorrhagic MMD was significantly greater than both ischemic MMD and HC (P < 0.05). The right MTG also showed higher CBF, and its associated fiber tract (arcuate fasciculus, AF) exhibited higher fractional anisotropy (FA) values in hemorrhagic MMD. Furthermore, the cortical thickness of the right MTG was positively correlated with its CBF values (r = 0.37, P = 0.046) and the right AF’s FA values (r = 0.67, P < 0.001). At last, the right AF’s FA values were found to be significantly correlated with cognitive performances within MMD patients. Conclusions – Hemorrhagic MMD shows increased cortical thickness on the right MTG in comparison with ischemic MMD and HC. The increased cortical thickness is associated with higher CBF values and increased integrity of the right AF. These findings are important to understand the clinical symptoms and pathophysiology of MMD and further applied to clinical practice.